Evaluation Standart Operational Prosedure Corporate Social Responbility - Hajan Hidayat; Yuricha Vittri Yanti (Journal of Applied Accounting and Taxation, 2016)
This research discusses the format of the financial statement made PKBL for use by business partners as a condition in the loan submission. The format of the financial statements statement of financial position is provided and profit/loss. The authors found a problem that is often business partners do not fill financial statements correctly so troublesome parties PKBL. This leads to slow lending process. Charging error caused by lack of understanding business partners against the financial report provided PKBL. Based on the basic provisions of the preparation of the financial statements, the author of menyimpulakan that the report provided PKBL yet eligible conditions i.e. financial statements can not be understood, irrelevant, unreliable and often does delay time in gathering financial statements.